Environmental social sciences : methods and research design - Vaccaro, Ismael; Smith, Eric Alden; Aswani, Shankar (Cambridge Cambridge University Press, 2010)
'The relationship between human communities and the environment is extremely complex. In order to resolve the issues involved with this relationship, interdisciplinary research combining natural sciences, social sciences, and humanities is necessary. Here, specialists summarise methods and research strategies for various aspects of social research devoted to environmental issues. Each chapter is illustrated with ethnographic and environmental examples, ranging from Australia to Amazonia, from Madagascar to the United States, and from prehistoric and historic cases to contemporary rural and urban ones. It deals with climate change, deforestation, environmental knowledge, natural reserves, politics and ownership of natural resources, and the effect of differing spatial and temporal scales. Contributing to the intellectual project of interdisciplinary environmental social science, this book shows the possibilities social science can provide to environmental studies and to larger global problems and thus will be of equal interest to social and natural scientists and policy makers'--
Machine generated contents note: 1. Introduction E. A. Smith and I. Vaccaro; 2. People, numbers, and natural resources: demography in environmental research O. Beltran; 3. Production decisions and time allocation: a guide to data collection R. Hames; 4. Analyzing the politics of natural resources: from theories of property rights to institutional analysis and beyond A. Poteete; 5. Extreme events, tipping points and vulnerability: methods in political economy of environment E. C. Jones; 6. Local communities and natural resources: ethnobiology in practice L. Zanotti, D. Glover and J. Sepez; 7. Mapping histories: cultural landscapes and walkabout methods V. Strang; 8. Metaphors and myths in news reports of an Amazonian lost tribe: society, environment and literary analysis C. Slater; 9. Water decision-makers in a desert city: text analysis and environmental social science Amber Wutich and C. Gravlee; 10. Linking human and natural systems: social networks, environment and ecology J. Johnson and D. Griffith; 11. Khat commodity chains in Madagascar: multi-sited ethnography at multiple scales L. Gezon; 12. Spatio-temporal methodologies in environmental anthropology: geographic information systems, remote sensing, landscape changes and local knowledge E. Brondizio and R. R. Chowdhury; 13. Deep time, diachronic change, and the integration of multi-scalar data: archaeological methods for exploring human-environment dynamics E. Jones; 14. Comparing trajectories of climate, class and production: an historical ecology of American yeomen M. Scholl, D. N. Murray and C. L. Crumley; 15. Anthropology and natural resource management: methodological integrations S. Aswani.
Includes index.
Keywords: Human ecology -- Research -- Methodology